Single Dose Abacavir Pharmacokinetics and Safety in Neonates Exposed to Human Immunodeficiency Virus (HIV). (22nd July 2020) - Bekker, Adrie; Decloedt, Eric H; Slade, Gretchen; Cotton, Mark F; Rabie, Helena; Cressey, Tim R
Abstract: Abacavir is a potential option for prophylaxis and early treatment of human immunodeficiency virus (HIV), but no data are available in neonates. Ten neonates administered a single abacavir dose of 8 mg/kg before 15 days of life had substantially higher exposures than those reported in infants and children, with no reported adverse events.